Does urbanisation have an impact on the trophic ecology of the Algerian hedgehog Atelerix algirus in northern Algeria? - Amina Zidane; Ilham Sahki-Benabbas; Mohamed Ayoub Rahal; Riadh Moulaî (Biodiversity Data Journal, 2024)
The Algerian hedgehog, which is an endemic Mediterranean species, is a nocturnal and terrestrial insectivorous mammal. Atelerix algirus’ populations are widespread in various habitats comprising human agglomeration, such as rural, suburban or natural ecosystems. However, the impact of the habitat’s characteristics on its diet remains unknown in Algeria. To contribute to a better understanding of this question, we have analysed 158 faeces samples of the Algerian hedgehog in three different areas: urban, suburban and natural area.The findings show that the Algerian hedgehog is an opportunistic species. It feeds on several classes of Arthropoda, but the harvester ant Messor barbarus dominates largely its menu with AR = 74.81% in the diverse habitats. Furthermore, the HAC and FCA analyses confirm the positive impact of the level of urbanisation and the anthropogenic activity on the Algerian hedgehog prey richness in the north of Algeria (79 prey species and 5574 individuals ingested in the urban area, compared to 64 prey species and 3188 individuals ingested in the natural zone).